The founding of the chair of comparative embryogeny at the Collège de France (1844) - Fischer, J L (Revue d'histoire des sciences, 1998)
The first chair of embryology was founded in 1844 at the College de France. Yet the founding met with hostility. The first occupant Victor Coste (1807-1873) was imposed on the institution. The administrator-professors of the College de France criticized the governmental procedure. Some professors, such as Georges-Louis Duvernoy, made a stand against the appointment of the young embryologist. Duvenoy continued for several years to protest against Coste's teachings at the College of France. But Coste was tacked by De Blainville and eventually Flourens. Credit should be given to Coste for having introduced a scientific embryology in France. The history of the founding of the chair of comparative embryogeny at the College de France is here described by drawing mainly on an umpublished archival source